Treacher Collins syndrome: clinical implications for the paediatrician-a new mutation in a severely affected newborn and comparison with three further patients with the same mutation, and review of the literature - ELÇİOĞLU, HURİYE NURSEL (SPRINGER, 2012)
Treacher Collins syndrome (TCS) is the most common and well-known mandibulofacial dysostosis caused by mutations in at least three genes involved in pre-rRNA transcription, the TCOF1, POLR1D and POLR1C genes. We present a severely affected male individual with TCS with a heterozygous de novo frameshift mutation within the TCOF1 gene (c.790_791delAG,p.Ser264GlnfsX7) and compare the clinical findings with three previously unpublished, milder affected individuals from two families with the same mutation. We elucidate typical clinical features of TCS and its clinical implications for the paediatrician and mandibulofacial surgeon, especially in severely affected individuals and give a short review of the literature. Conclusion:The clinical data of these three families illustrate that the phenotype associated with this specific mutation has a wide intra- and interfamilial variability, which confirms that variable expressivity in carriers of TCOF1 mutations is not a simple consequence of the mutation but might be modified by the combination of genetic, environmental and stochastic factors. Being such a highly complex disease treatment of individuals with TCS should be tailored to the specific needs of each individual, preferably by a multidisciplinary team consisting of paediatricians, craniofacial surgeons and geneticists.
Keywords: Treacher Collins syndrome; Franceschetti syndrome; Severe phenotype; TCOF1 mutation; UPPER AIRWAY-OBSTRUCTION; MANDIBULAR DISTRACTION; GENE-PRODUCT; SLEEP-APNEA; TCOF1; PATHOGENESIS; ETIOLOGY; REVEALS; INFANTS; CELLS